THE USAGE OF TRIMETAZIDINE AND SULODEXIL TO PREVENT TRANSFORMATION OF A NON-Q MI INTO A Q-MI - A. A. Abdullaev; U. A. Islamova; R. M. Gafurova (Российский кардиологический журнал, 2001)
In main group 104 patients of Q-myocardial infarction were treated during the first 7 days of the moment it entered a hospital by trimetazidine and sulodexide combine with the traditional treatment (nytroconnection, aspirin, beta- adrenoblocators). In control group 130 patients were treated only by traditional treatments. The blood of 62 patients from main group and 65 patients from control group was examined on thrombin’s time, partly activated tromboplastine’s time and thrombocite aggregation in dynamics three times in the first, the third and the 7-th days of observation. There were undergoing daily ECG-monitoring on Cholter. The results of treatments were valued in both groups according the number of patients with Q-myocardial infarction, average daily frequency of attacks angina pectoris, the number and duration of episodes painless myocardial ishemic, changes of parameter of hemostasis. It was exposed, that in main group Q-myocardial infarction was developed only in 2,9% patients and in 14,6% patients in control group. The average daily frequency of attacks of angina pectoris, the number of episodes of painless myocardial ishemic and their duration in main group were nearly 2 times less them in control group. It was accompanied by improvement hemostasis in main group. Thus, trimetazidine and sulodexide promote the prophylaxis Q-myocardial infarction.